Antibiotic Resistance Patterns of Pseudomonas Aeruginosa and Escherichia Coli Isolates from Three Hospitals In Kumasi - Duredoh, Freeman George (2011)
A Thesis submitted to the Department of Pharmaceutics in partial fulfilment of the requirements for the award of the Master of Philosophy (M.Phil.) Degree in Pharmaceutical Microbiology